2015
DOI: 10.2174/1871520615666141216150659
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mitochondrial Citrate Transport in Breast Cancer Cell Lines

Abstract: Lipogenesis is considered to be a very important aspect of cancer metabolism and targeting de novo lipid synthesis or related pathways are among novel approaches to treat cancer. Many targets of the pathway including ATP-citrate lyase (ACLY), acetyl-CoA carboxylase and fatty acid synthase have been evaluated for their potential in cancer treatment. However the role of citrate transport protein (CTP), another important component of lipogenesis pathway, is not well known for cancer metabolism and cell survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…In a similar manner, the regulation of citrate transport may largely account the lack of significant changes in extracellular citrate. [ 37 ]. If citrate and pyruvate are not being actively transported across the membrane then any alteration in their production with the cell will not be reflected in the culture medium.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar manner, the regulation of citrate transport may largely account the lack of significant changes in extracellular citrate. [ 37 ]. If citrate and pyruvate are not being actively transported across the membrane then any alteration in their production with the cell will not be reflected in the culture medium.…”
Section: Resultsmentioning
confidence: 99%
“…The identified compound was also reported to inhibit both isoforms of ACC, making it impossible to rule out the role of off-target effects on the in vivo experimental outcomes. Interestingly, a competitive inhibitor of the mitochondrial citrate transport protein (CTP) fits this same structural class (Aluvila et al, 2010), and it was recently reported that this small molecule reduces cytoplasmic citrate levels in MCF-7 and MDA-MB-231 BC cells, reducing cell viability by 38.3% and 36.4%, respectively (Ozkaya et al, 2015).…”
Section: Targeting Dependence On Fa: Inhibiting Acly and Accmentioning
confidence: 99%
“…Several studies demonstrated that inhibition of CTP impaired LPS-induced activation of macrophages and DCs (Infantino et al, 2011;Everts et al, 2014). Because we found that 4-chloro-3-{[(3-nitrophenyl) amino]sulfonyl}benzoic acid, a CTP inhibitor (Ozkaya et al, 2015), slightly reduced LPS-induced expression of CD40 and CD86 in WT DCs (Figure 6A), we also considered that the increased citrate affected DC maturation in the cytosol. ATP citrate lyase (ACLY) is a cytosolic enzyme that converts citrate to oxaloacetate and acetyl-CoA, a key step for FAS.…”
Section: (Legend Continued On Next Page)mentioning
confidence: 99%